Wastewater Management in Africa: Challenges and Recommendations - Ejovwokeoghene Joseph Omohwovo (SAGE Publishing, 2024)
In Africa, the growing population and industrial growth have resulted in a notable increase in wastewater generation, affecting the quality of water in the region. Wastewater treatment plays a crucial role in safeguarding the environment, public health, aquatic organisms, and water resources, reducing environmental impact, and adhering to regulations. However, the current methods for treating wastewater in Africa fall short of these goals, resulting in substantially poor environmental and health outcomes and inadequate provision of safe water and essential sanitation. Poor wastewater management in several African countries has led to severe health risks for humans, animals, and aquatic ecosystems. This poses a particular threat to vulnerable groups like children, women, and the disabled residing in rural and remote areas with limited access to healthcare. Hence, this article aims to shine a spotlight on the difficulties in managing wastewater in Africa and to recommend several plausible strategies to tackle this issue. A literature search to find the most recent and relevant research papers from various databases, such as Scopus, Web of Science, PubMed, and Google Scholar, along with resources from the World Health Organization, was conducted. The selection criteria focused on including the most recent and relevant publications published in English to facilitate comprehension, analysis, and interpretation of the secondary data. Essentially, addressing the challenge of wastewater management in Africa requires developing indigenous innovative technologies, transitioning to a sustainable economy, establishing wastewater treatment infrastructures in rural and remote areas, enhancing operation and maintenance practices, training treatment facility workers, improving electricity supply, strengthening government participation and support, encouraging public involvement, setting local water quality benchmarks, and international financial and technical support. By tackling the problem of insufficient wastewater treatment in Africa, it is possible to achieve Sustainable Development Goal 6, which centers on ensuring clean water and sanitation for all.